What to teach when we teach digital strategy? An exploration of the nascent field - Cepa, Katharina; Schildt, Henri (Long range planning, 2023)
Companies are increasingly pursuing competitive advantage through innovative use of advanced information technologies, such as artificial intelligence. Management education must prepare students with the skills and knowledge needed to function effectively and ethically in this increasingly digitalized business environment. Yet, we have no consensus on what constitutes digital strategy, let alone how the topic ought to be taught. To advance the emerging subdiscipline of digital strategy, this article takes stock of the teaching in this nascent domain. We conducted an inductive analysis of twelve postgraduate modules and fifteen massive open online courses (MOOCs) to provide an empirically grounded framework. Our analysis categorizes digital strategy-related module content into four domains, constituted by thirteen topic areas. We further identify five distinct course profiles that digital strategy modules typically follow. This article contributes to the strategic management discipline by providing an exploration of digital strategy teaching and offering concrete guidelines for teaching digital strategy in business schools and universities, either as a module on its own right or as part of an existing strategy module.